Marine waste recycled low-carbon building material reaching B-class fireproofing and preparation method thereof

CN122914548APending Publication Date: 2026-10-16GUANGZHOU JUWEI MATERIALS PARTNERSHIP (LLP)
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611286724.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-24
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

现有由回收塑料制备的仿木建材,其防火性能大多较差,通常仅能达到或无法达到GB 8624标准中的B级要求,这严重限制了其在建筑外墙、阳台栏杆、户外平台等有严格防火规范场所的应用

Benefits of technology

确切的B级防火安全性:本发明制备的建材,经检测其防火性能达到《GB 8624建筑材料及制品燃烧性能分级》中的B1级(B级)标准。此效果源于其独特的结构设计:致密的高分子聚合物复合塑料弹性体壳层完整包覆了内部混合料芯层,在燃烧条件下,壳层能有效延缓火焰蔓延,形成高效的防火屏障。这一特性使得产品可应用于对防火有明确要求的建筑部位,拓展了回收塑料建材的应用边界。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122914548A_ABST
    Figure CN122914548A_ABST
Patent Text Reader

Abstract

The application discloses a kind of ocean garbage recycled low-carbon building materials reaching B-grade fire prevention and a preparation method thereof, and belongs to the technical field of solid waste resource utilization and functional building fireproof material.The core layer raw material is obtained by crushing more than ten kinds of mixed high molecular polymers such as PE, PET, PP, PU, PA, PS, ABS and rubber in ocean garbage to a particle size of less than 0.5 cm, and a PS / HDPE / PET-based polymer composite plastic elastomer is heated at a weight ratio of 1:1;first, the core layer raw material is injected into the mold center through B channel to form a core layer, and after 5 minutes, the composite plastic elastomer is injected into the mold through A channel to completely cover the core layer to form a shell layer;after mold pressing, cooling and demolding, the surface is treated by hot transfer printing wood grain to obtain a green low-carbon fireproof building material with core-shell double-layer structure.The weight of ocean garbage crushed material in the finished product is not less than 50%, and the offcut and unqualified product can be fully recycled and reused.The dense shell layer covering structure effectively blocks oxygen and delays flame spread under burning conditions.The product meets the GB 8624 B1 fireproof standard, has the advantages of low carbon, environmental protection, weather resistance, corrosion resistance and recyclability, and is suitable for outdoor projects such as seaside walkway, railing, pavilion and wharf.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the technical field of solid waste resource utilization and functional building fireproof materials, and particularly relates to a low-carbon building material made from marine debris that can achieve the Class B fire resistance rating in GB 8624 standard, and its preparation method. Background Technology

[0002] Marine debris refers to persistent, man-made, or processed solid waste in the marine and coastal environment. Monitoring results show that floating debris on the sea surface mainly consists of plastic bags, floating wood, buoys, and plastic bottles, with plastic debris being the most abundant, accounting for 41%. Plastic debris is the most prevalent type of debris on beaches, accounting for 66%. Seabed debris mainly consists of glass bottles, plastic bags, beverage cans, and fishing nets. Statistics show that polymer-based debris is the most abundant, accounting for 71.84%, followed by foam (8.17%), nylon (5.44%), rubber (5.06%), and plastic fragments are the most common type of debris, accounting for 33.58%.

[0003] Zhang Yanfeng, deputy dean of research at the School of Chemistry, Xi'an Jiaotong University, said that the types of recycled plastics are diverse, and many products are not only made of one material, but also some products cannot be recycled after processing. "This is not a technical problem, but a practical problem, and it will take decades or even hundreds of years to solve it." Existing wood-look building materials made from recycled plastics generally have poor fire resistance, typically only meeting or failing to meet the Class B requirements of the GB 8624 standard. This severely limits their application in areas with strict fire safety regulations, such as building exteriors, balcony railings, and outdoor platforms. Current technologies largely focus on using relatively pure recycled plastics to produce basic wood-look products, resulting in limited functionality and significant shortcomings in fire safety, failing to meet the higher demands of modern architecture for both environmental friendliness and safety in materials. Summary of the Invention

[0004] The purpose of this invention is to overcome the shortcomings of existing technologies and provide a method for preparing a double-layer composite building material that meets the GB 8624 B1 fire resistance standard and also possesses green and low-carbon characteristics, using marine debris as the main raw material. This method is based on a unique dual-channel sequential injection molding process to construct a core-shell structure with fire-resistant properties.

[0005] To achieve the above objectives, the present invention adopts the following technical solution: a method for preparing low-carbon building materials made from recycled marine waste that achieve Class B fire resistance, comprising the following steps: Step (1) Pre-treatment of marine debris: Marine debris or land debris containing more than ten kinds of mixed polymers, such as polyethylene (PE), polyethylene terephthalate (PET), polypropylene (PP), polyurethane (PU), polyamide (PA), polystyrene (PS), high-density polyethylene (HDPE), polyvinyl chloride (PVC), acrylonitrile-butadiene-styrene copolymer (ABS), and rubber, is recycled and sent to a non-sorting crushing equipment for crushing to form crushed material A (containing large and small particles); then it is screened by a particle screening equipment, and crushed material with a particle size of less than 0.5 cm is selected as mixed plastic crushed material B; the washing uses recycled water through a circulating filter, and after washing and air drying, clean mixed plastic crushed material B is obtained.

[0006] Step (2) Preparation of the coating material: Polystyrene (PS) is used as the main raw material, combined with high-density polyethylene (HDPE) and polyethylene terephthalate (PET) to form a polymer composite plastic elastomer. The PS accounts for 50%–60%, HDPE 30%–40%, and PET 10%–20%, with the sum of their weight percentages being 100%. The melting point of this composite plastic elastomer is 150°C.

[0007] Step (3) Double-layer injection molding: The mixed plastic crushed material B obtained in step (1) and the polymer composite plastic elastomer obtained in step (2) are heated separately at a weight ratio of 1:1 and then conveyed to a dual-channel injection molding machine. The injection molding process includes: first, the heated mixed plastic crushed material B is injected into the center of the mold through channel B to form a core layer; after the injection of channel B is completed, after an interval of 5 minutes, the heated polymer composite plastic elastomer is injected into the mold through channel A to completely cover the core layer to form a shell layer; after molding and cooling for 20-30 minutes, the mold is removed to obtain a green low-carbon fireproof building material blank C with a core-shell double-layer structure.

[0008] Step (4) Post-processing: The blank C is inspected for quality. Qualified products are subjected to surface wood grain heat transfer treatment to obtain low-carbon building materials (such as outdoor flooring, railings, walkway boards, etc.) that meet the GB 8624 B1 fireproof standard. Unqualified products are crushed and recycled as raw materials.

[0009] The mixed plastic crushed material B accounts for no less than 50% of the total weight of the finished product, and the flow channel waste and unqualified products generated during the production process are recycled as raw materials after being crushed.

[0010] Compared with the prior art, the technical solution of the present invention has the following advantages: Accurate Class B Fire Safety: The building materials prepared by this invention have been tested and found to meet the Class B1 (Class B) standard in the "Classification of Burning Performance of Building Materials and Products" (GB 8624). This effect stems from its unique structural design: a dense polymer composite plastic elastomer shell completely covers the internal mixture core layer. Under combustion conditions, the shell effectively slows the spread of flames, forming a highly efficient fire barrier. This characteristic allows the product to be applied to building components with specific fire protection requirements, expanding the application boundaries of recycled plastic building materials.

[0011] Green and low-carbon attributes at the source: Using marine debris as the main raw material (accounting for no less than 50%), reducing the consumption of natural wood and plastic pollution at the source, the entire production process can achieve full recycling of scraps, and the carbon footprint is far lower than that of traditional building material manufacturing, which meets the requirements of green, low-carbon and circular economy.

[0012] Synergistic performance and high durability: The unique dual-layer structure leverages the synergistic effect of materials. The core layer primarily serves as a filler and support layer, significantly reducing raw material costs; the shell layer provides excellent mechanical strength, weather resistance, and waterproof and corrosion-resistant properties. This results in a long product lifespan and low maintenance costs.

[0013] Easy to clean and maintain: The surface of the product of this invention is made of composite plastic material, which is easier to clean and maintain than traditional wood. It can be simply cleaned with detergent and water, without the need for complicated maintenance processes such as painting or waxing.

[0014] Fully recyclable and reusable: Since polymer composite plastic elastomers can be recycled and reused, the products of this invention can also be recycled and reused. The amount of marine debris used is not less than 50%. After the products are used, they can be continuously recycled and reproduced, achieving the goals of circular economy, ecological environment protection, and environmental protection and carbon reduction.

[0015] Highly compatible raw material processing: This invention can use more than 10 kinds of polymers mixed together (most on the market only have 2 to 3 kinds, mainly HDPE, PP and PS), and can process marine garbage with complex composition without fine sorting, truly realizing the high-value utilization of mixed waste that cannot be finely classified. Attached Figure Description

[0016] Figure 1 is a flowchart of the preparation process of the present invention (S1-S16 full process).

[0017] Figure 2 is a schematic diagram of the core-shell cross-sectional structure of the product C of the present invention, wherein (1) is the core layer (marine waste mixed plastic crushed material B), and (2) is the shell layer (polymer composite plastic elastomer).

[0018] Figure 3 is a schematic diagram of the timing of the dual-channel injection coating process of the present invention. Detailed Implementation

[0019] The present invention will now be described in further detail with reference to the accompanying drawings and specific embodiments.

[0020] Example 1: Basic Preparation Process Step S1: Raw material preparation. Collect marine debris (including mixtures of more than ten kinds of polymers such as PE, PET, PP, PU, ​​PA, PS, HDPE, PVC, ABS, and rubber) and / or mixed polymers from land debris that cannot be further classified.

[0021] Step S2: Crushing process. The raw material S1 is fed into a non-sorting crushing device for crushing to form crushed material A (containing large and small particles).

[0022] Step S3: Particle screening. The crushed material A is circulated and screened through a particle screening device. Particles smaller than 0.5cm pass through the screening, while particles larger than 0.5cm are returned to S2 for further crushing.

[0023] Step S4: Washing and Drying. The screened crushed material A is conveyed to the washing machine via a conveyor belt, where it is washed and dried using recycled water. Since marine debris mainly consists of mud, gravel, salt, and volcanic ash, crushing it into small particles makes it easy to wash, dries quickly, and does not cause water pollution.

[0024] Step S5: Obtain material B. After washing, air drying, and sieving, the crushed material with a particle size of less than 0.5 cm is the mixed plastic crushed material B.

[0025] Step S6: Preparation of the polymer composite plastic elastomer. It is prepared by kneading polystyrene (PS) as the main raw material (50%~60%), combined with high-density polyethylene (HDPE) (30%~40%) and polyethylene terephthalate (PET) (10%~20%). The polymerization process includes an autoclave, a tower reactor, and a kneader. High-efficiency kneading of the polymer composite plastic elastomer is achieved by controlling the temperature and residence time of the reactants. The elastomer has a melting point of 150℃.

[0026] Step S7: Mixing and feeding. Feed S5 material B (approximately 50% by weight) and S6 polymer composite plastic elastomer (approximately 50% by weight) separately and heat them separately.

[0027] Step S8: Dual-channel injection molding. The heated S5 material B is injected into the center of the mold through channel B to form the core layer. After channel B injection is complete, wait 5 minutes. Then, the heated S6 polymer composite plastic elastomer is injected into the mold through channel A, completely covering the core layer to form the shell layer. The mold is then molded using injection molding, and waits 20-30 minutes.

[0028] Steps S9-S10: Sprue Cooling Control. Through sprue design and water flow control, the molten material is cooled and solidified in the mold, reducing product defects and flaws. After cooling, the product is demolded manually or automatically to obtain product C. After demolding, product C is obtained. Through the specific injection molding sequence described above, product C forms a stable core-shell double-layer structure, with the core layer being S5 marine waste mixed plastic crushed material B, and the shell layer being S6 high-molecular polymer composite plastic elastomer. As shown in Figure 2, the shell layer (2) completely encloses the core layer (1). When exposed to a fire source, the shell layer (2) acts as the first barrier, effectively delaying the combustion process. This unique core-shell encapsulation structure is key to achieving Class B fire resistance.

[0029] Step S11: Product C is a long, rectangular block used for outdoor flooring, railings, and walkways. By cutting Product C, a two-layer structure is clearly visible: the S6 polymer composite plastic elastomer completely encapsulates the S1 marine debris fragments.

[0030] Steps S12-S13: Product C undergoes quality screening using manual or video identification. Products that pass screening are sent to the heat transfer process for wood grain heat transfer treatment, producing finished green, low-carbon, fire-resistant building materials such as outdoor flooring, railings, and walkways, which are then packaged and shipped. Products that fail screening are classified as defective products D and sent for recycling and shredding.

[0031] Steps S14-S16: Defective product D and runner waste generated during demolding are sent to the crushing and pulverizing process, crushed into material E, and then returned to S7 as raw material for recycling.

[0032] Example 2: Verification of different raw material ratios Using the same process steps as in Example 1, only the combination of marine debris raw materials was changed: Group A used a mixture of five polymers: PE, PET, PP, PU, ​​and PA; Group B used a mixture of six polymers: PE, PET, PP, PS, ABS, and rubber; and Group C used a mixture of ten polymers: PE, PET, PP, PU, ​​PA, PS, HDPE, PVC, ABS, and rubber.

[0033] All three groups were subjected to dual-channel sequential injection molding with composite plastic elastomers at a weight ratio of 1:1. The results showed that all three groups formed a stable core-shell bilayer structure, and due to the complete shell coverage, the surface quality and mechanical properties of all three products met the requirements for outdoor building materials. Group C (a mixture of ten materials) exhibited the best raw material compatibility, verifying the high tolerance of this invention to complex mixed marine debris.

[0034] Example 3: Fire resistance performance verification The product C blank obtained in Example 1 was used to make a standard sample, and its fire resistance performance was tested according to national standards: (1) According to GB / T 8626 "Test Method for Combustibility of Building Materials", the burning length and flame spread after ignition of the sample met the standard requirements. (2) According to GB 8624 "Classification of Combustion Performance of Building Materials and Products", the results showed that the building material product prepared by the present invention reached the B1 level (B level) fire resistance standard. The B1 level fire resistance effect is due to the unique core-shell structure design of the present invention: the dense polymer composite plastic elastomer shell completely covers the complex and flammable marine waste mixed core layer. Under combustion conditions, the shell layer can effectively block oxygen and delay the spread of flame to the core layer, forming a highly efficient fire barrier. This structural feature cannot be achieved by simple co-extrusion or ordinary mixed injection molding process.

[0035] Example 4: Cyclic Regeneration Verification Waste material from the flow channel and defective product D generated during the production process of Example 1 were collected, pulverized into material E in S16, and then mixed with new material at a ratio of 30% and returned to S7 for reuse. After five consecutive cycles, the core-shell structure of product C remained stable, its mechanical properties showed no significant decline, and its fire resistance still met the B1 standard requirements. This verifies that the product of this invention can truly achieve a closed-loop circular economy of "marine waste → building materials → recycling → reproduction".

[0036] This invention is not limited to the specific embodiments described above. Any equivalent substitutions or improvements made based on the technical solutions of this invention are within the scope of protection of this invention.

Claims

1. A method for preparing low-carbon building materials made from recycled marine debris that achieve Class B fire resistance, characterized in that, Includes the following steps: (1) Marine debris pretreatment: Waste mixed polymers containing at least three of the following: polyethylene (PE), polyethylene terephthalate (PET), polypropylene (PP), polyurethane (PU), polyamide (PA), polystyrene (PS), high-density polyethylene (HDPE), polyvinyl chloride (PVC), acrylonitrile-butadiene-styrene copolymer (ABS), and rubber are recycled, cleaned, and dried, and then sent to a non-sorting crushing equipment for crushing. After being screened by a particle screening equipment, materials with a particle size of less than 0.5 cm are selected as mixed plastic crushed material B. (2) Preparation of coating material: Polystyrene PS is used as the main raw material, combined with high-density polyethylene HDPE and polyethylene terephthalate PET to form a high molecular polymer composite plastic elastomer, wherein polystyrene PS accounts for 50%~60%, high-density polyethylene HDPE accounts for 30%~40%, and polyethylene terephthalate PET accounts for 10%~20%, and the sum of the weight percentages of the three is 100%; (3) Double-layer injection molding: The mixed plastic crushed material B obtained in step (1) and the polymer composite plastic elastomer obtained in step (2) are heated separately at a weight ratio of 1:1 and then conveyed to a dual-channel injection molding machine; firstly, the heated mixed plastic crushed material B is injected into the center of the mold through channel B to form a core layer; after the injection of channel B is completed, after an interval of 5 minutes, the heated polymer composite plastic elastomer is injected into the mold through channel A to completely cover the core layer to form a shell layer; after molding and cooling for 20-30 minutes, the mold is demolded to obtain a green low-carbon fireproof building material blank with a core-shell double-layer structure; (4) Post-processing: The blank is inspected for quality. Qualified products are subjected to surface wood grain heat transfer treatment to obtain low-carbon building materials that meet the GB8624 B1 fireproof standard. Among them, the mixed plastic crushed material B accounts for no less than 50% of the total weight of the finished product. Unqualified products and flow channel waste generated during the production process are crushed and recycled as raw materials.

2. The preparation method according to claim 1, characterized in that: The mixed polymer waste mentioned in step (1) contains more than ten different types of polymers, and the sources include mixed plastic waste that cannot be further classified from marine debris and / or terrestrial debris.

3. The preparation method according to claim 1, characterized in that: The time interval after the B channel is filled in step (3) is 5 minutes, and the molding cooling time is 20~30 minutes.

4. The preparation method according to claim 1, characterized in that: In step (3), the shell layer is uniformly covered on the outside of the core layer, and the shell layer completely seals the core layer to form a continuous fire barrier structure.

5. The preparation method according to claim 1, characterized in that: The melting point of the polymer composite plastic elastomer mentioned in step (2) is 150℃.

6. The preparation method according to any one of claims 1 to 5, characterized in that: The fire resistance of the building materials prepared by the method meets the B1 standard in GB 8624 "Classification of Combustion Performance of Building Materials and Products" and passes the test in GB / T 8626 "Test Method for Combustion of Building Materials".

7. A low-carbon building material made from recycled marine debris, achieving a Class B fire resistance rating, prepared by the method according to any one of claims 1 to 6, characterized in that... The building material has a core-shell double-layer structure: the core layer is composed of mixed plastic crushed material from marine debris, and the shell layer is composed of high molecular polymer composite plastic elastomer, with the shell layer completely covering the outside of the core layer; the fire resistance of the building material meets the GB8624 B1 standard, the marine debris component accounts for no less than 50% of the total weight of the finished product, and the product can be recycled and reused.